The Innocence of a Young Man with Down Syndrome versus the Barbarity of the Zionist Entity: Visual Crimes through the Lens of International Covenants and Laws - Nassira Djeghri Zarouta (Journal of Science and Knowledge Horizons, 2025)
The paper discusses the visualization of young man from Palestine, Mohammad Bahar, an individual with Down syndrome who became a victim when the Zionist entity attacked Gaza. The article aims to reveal the explicit (denotative) and implicit (connotative) meaning, which is in the chosen AI-generated image, emphasizing their purpose as visual witnesses to events that are simulated, and go beyond the textual description. This study adopts the semiotic framework by Roland Barthes to examine how the visual signs create multiple layers of meaning and how these layers interact with the international humanitarian law and conventions regarding the protection of civilians, especially persons with disabilities. The findings indicate that the visual crimes committed by the occupation are not only blatant crimes against international treaties but also produce symbolic and cultural codes that make the whole world aware of the horrors that vulnerable groups experience. This interdisciplinary method highlights the strength of images as shaping the opinions of people and shows that the discourse of visual images can be used as potential evidence to systematic human rights violation.